Projekt "Odpisani" in odpis gradiva v Univerzitetni knjižnici Maribor - Lončar, Nina (Knjižnica, 2010)
The process of de-acquisition and weeding is based on the same selection criteria as acquisition of library materials and requires profound knowledge and understanding of a library collection. The author presents the methodology and the process of weeding and de-acquisition at the University Library of Maribor. The case study is the project "The Written-Offs". The lights and art works made out of damaged books exhibited in this project attracted a lot of media and public attention. The results and experiences drawn from the project "The Written-Offs" show a possible way to promote libraries.
Keywords: knjižnično gradivo; izločanje gradiva; odpis gradiva; projekti; Univerzitetna knjižnica Maribor